The rite in the school context - da Silva, Jailson (2012)
Assuming that all action is enveloped by the symbolic ritual; that symbolic thought is always an assimilation which reminds us of accommodating attitudes; and that the human being seeks to give meaning to their existence, the purpose of this article is to describe  a rite of initiation and its symbolic implications in the school context. The research is descriptive and field research in the municipal school network of João Pessoa / PB. The qualitative approach and the symbolic hermeneutics used in the analysis aims to describe the symbolic forms of the selected rite. As a first result of our study, we analyzed the initiation rite of the first day of class in its reality as a social and collective fact, as a being a structural element that organizes the world and the consciousness of the individual. It was identified that the ritual action establishes meanings and teaches students in the school context.